We Are All in the Same Boat: Cross-Border Spillovers of Climate Shocks through International Trade and Supply Chain - Alan Feng; Haishi Li; Yulin Wang (Center for Economic Studies and ifo Institute (CESifo), 2023)
Are land locked countries subject to sea-level rise risk? We highlight a new mechanism by which physical climate shocks affects countries' macro-financial performance: the cross-border spillover effects that propagate through international trade. Basing our findings on historical data between 1970 and 2019, we find that climate disasters that strike the transport infrastructure – ports – decrease the affected country's imports and exports and reduce economic output in major trade partner (both upstream and downstream) countries. Climate disasters reduce stock market returns in the aggregate market and tradable sectors of the major trade partner countries. Exposures to foreign long-term climate change risks reduce the asset price valuations of the tradable sectors at home. As a result, climate adaptation efforts in one country can have a positive impact on macro-financial performance and stability in other countries through international trade.
Keywords: F42; G14; Q54; 330; climate risks; international trade; infrastructure; macro-financial stability